Fish Community Structure in Lake Sayok in Telabang Hilir Hamlet Subah Village Tayan Hilir Sub-district Sanggau District - Andri Andri; Ahmad Mulyadi Sirojul; Inpurwanto Inpurwanto (Fakultas Pertanian Universitas Tanjungpura, 2020)
Lake Sayok has been utilized by the community for fishing. Its close location to oil palm plantations affects the quality of the waters. This study aims to identify the fish community structure in Lake Sayok, Telabang Hilir Hamlet, Subah Village, Tayan Hilir Sub-district, Sanggau District including Relative Abundance (KR%), Species Diversity (H'), Domination (C), and Uniformity (E), as well as supporting physical, chemical and biological parameters in aquatic environments. The research used a purposive sampling method in which the determination of station points was divided into 4 points to represent the area of the lake. The result showed that the number of fish species reached 985 species individuals consisting of 9 families and 20 species. The highest relative abundance value was Kumpang fish (Belontia hasselti) with a value of 12.18% and the lowest abundance was Lais species (Belodontichthys dinema) with a value of 0.91%. The Diversity Index value was 2.70 included in the medium category. The Dominance Index value was 0.08 included in the low category. The Uniformity Index value reaches 0.90 indicating the high uniformity of the type at the station with even distribution or the number of individuals of each species is relatively the same.